The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12912-023-01432-4
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an evaluation index system for undergraduate nursing teachers’ curriculum humanistic competence: a Delphi study in China

Zihan Yang,
Huimin Zhai,
Sijing Liang

Abstract: Background The curriculum humanistic competence of nursing teachers is important to cultivate the humanistic qualities of undergraduate nursing students. However, there are no evaluation tools for the curriculum humanistic competence of undergraduate nursing teachers in China. Objective To develop an index system to evaluate the curriculum humanistic competence of undergraduate nursing teachers. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Studies have shown that knowledge level, as one of the core competencies of oncology nurses, and nursing staff with extensive expertise are more competent in CIPN care. 24 Knowledge-attitude-behavior theory (KAP) refers to the idea that individuals can form beliefs and eventually achieve behavioral change through repeated reflection after acquiring knowledge, 25 and this theory has made an important contribution to the long development of nursing. Hospital administrators can hold relevant trainings based on this theory to enhance the professional level of nursing staff, clarify professional knowledge through teaching, and contextual training to achieve the integration of knowledge and practice.…”
Section: Doctors Pay Little Attention To Cipnmentioning
confidence: 99%
“…Studies have shown that knowledge level, as one of the core competencies of oncology nurses, and nursing staff with extensive expertise are more competent in CIPN care. 24 Knowledge-attitude-behavior theory (KAP) refers to the idea that individuals can form beliefs and eventually achieve behavioral change through repeated reflection after acquiring knowledge, 25 and this theory has made an important contribution to the long development of nursing. Hospital administrators can hold relevant trainings based on this theory to enhance the professional level of nursing staff, clarify professional knowledge through teaching, and contextual training to achieve the integration of knowledge and practice.…”
Section: Doctors Pay Little Attention To Cipnmentioning
confidence: 99%